A escrita inventada e o uso das letras móveis com crianças de cinco anos - Andressa Camargos Macêdo (2019)
This research aims to evaluate the results of two Invented Writing Programs: in the first one, the children's metalinguistic reflection is mediated without the use of moveable alphabet; otherwise the second one is mediated with the use of moveable alphabet. The study participants were 5-year-old children from a municipal school in Belo Horizonte. The investigation was developed from August to October in 2017, considering all the meetings with the children. Two questions grounded this study: Will children who participate in the Invented Writing Program present more advanced writing strategies and hypotheses than the ones who do not participate in such a program? Will children who participate in the Invented Writing Program with the use of moveable alphabet present more advanced strategies and hypotheses of writing than the ones who participate in the program without the use of it? In this study, it was adopted the intervention research as an investigation perspective. Word writing tests were applied in order to verify the children’s conceptual level of writing before (pre-tests) and after (post-tests) the program’s accomplishment. All children in the surveyed class participated in literacy, syllabic awareness, and word reading tests. From the performance of the children in these tests, three research groups were formed: two experimental groups and one control group. The group which participated in the Invented Writing Program with the use of moveable alphabet was identified as Experimental Group 1. And, the group which participated in the Invented Writing Program without the use of moveable alphabet was identified as Experimental Group 2. Then, the group of children with which the Invented Writing Program was not developed was identified as Control Group. This research is related to authors who discuss the initial learning of writing and also, Invented Writing Programs. Initial hypotheses were confirmed in the survey results. Children who participated in the Invented Writing Program presented more advanced hypotheses regarding the quality of their invented post-test writing than those who did not participate in the writing intervention program. Besides, the children who participated in the Invented Writing Program with the use of moveable alphabet presented more advanced hypotheses regarding the quality of their invented writing in the scope of the post-test, than the children who are part of the program without the use of moveable alphabet. This research relies on contributing to the pedagogical practices in the classroom, providing elements on the impacts of two Invented Writing Programs (without and with the use of moveable alphabet) and the children’s writing processes and strategies.